Trails for local breeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Given FAO s role in drawing up the Global Strategy for the Management of Farm Animal Genetic Resources, it is only natural that its website should offer the best starting point for this subject.